MODELLING OF WAX CRYSTALLIZATION IN SOLVENT DEW AXING SCRAPED SURF ACE EXCHANGERS AND CHILLERS - MOKHLIF, NASSIR DHAMIN (2013)
The wax removal process using scraped surface exchangers and chillers in a solvent dewaxing unit is the most common industrial technology for the production of lubricant oils. The proper thennal design and control of the dewaxing process in these chilling machines is essential for a high quality product. The quality of the desired product is based on the control of the cooling rate and the wax crystallization process. Therefore, an appropriate mathematical model is required to simulate the dewaxing process for such complex wax-oil-solvent mixtures. A successful mathematical model requires a good estimation of the waxy oil-solvent properties, heat transfer characteristics, and wax crystal formation processes. To the best knowledge of the researchers, such coupling model for real solvent dewmdng unit does not presented in the literatures so far. In the present work, a reliable estimation model which comprised experimental and theoretical tools was developed.